Pengaruh Kecerdasan Intelektual , Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Karyawan (Pada Karyawan Universitas Islam Malang) - Yazid Afif; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this research is to discuss and analyze intellectual intelligence, emotional intelligence, and spiritual intelligence on employee performance either partially or simultaneously or together. The population and sample used were all employees of the Islamic University of Malang, totaling 70 people. Data collection through questionnaires. Data analysis in this study used SPSS version 21. The sampling technique used a questionnaire with a rikert scale and the data testing techniques used in this study used validity tests, reliability tests, normality tests, classical assumption tests, multiple linear regression analysis, F test and t testThe results obtained from the evaluation and analysis show that intellectual intelligence has a significant positive effect, emotional intelligence has a significant positive effect on employee performance, while spiritual intelligence has a significant positive effect on employee performance. Testing intellectual intelligence, and spiritual intelligence have a significant positive effect on employee performance. Keywords: Intellectual Intelligence, Emotional Intelligence, And Spiritual Intelligence, Employee Performance.